(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2015)
An experiment was conducted at the experimental field of Bangladesh Rice Research Institute (BRRI), Gazipur during T. Aman season 2007. Ten maintainer lines were evaluated to identify most diverse maintainer lines in respect of morphological traits for developing heterotic rice hybrids based on clustering and days to maturity. Based on mean values of different morphological traits and maturity, 10 maintainer lines were classified into four distinct clusters. Maximum Euclidean distance from centroids was observed in cluster 2 whereas cluster 3 and 4 found in the centroids. Most of the maintainer lines were grouped into early and medium maturing clusters while the remaining two lines were clustered into very early and late maturing clusters. Very early maturing group contained maintainer line (D.ShanB) with dissi cyto source and fell into cluster 3. It had short plant stature with short flag leaf but had high spikelet fertility and thousand grain weight. Early maturing group contained maintainer lines having 4 different cyto sources revealed early maturing group featured with cyto source variation with high panicle number/m2 and very good yield potentiality. Grouping the maintainer lines on the basis of maturity period yield per plot was proportionally higher in late maturing line. Only a single line Gan46B fell into late maturing group and had highest yield. This fact suggests possibility of corresponding CMS line of Gan46B could be used as female if restorer lines are selected from early maturing group. Medium maturing group had some added advantage like medium duration with diverse cyto sources and good yielding ability. If restorer lines are selected from late maturing group with high yield potentiality proper hybrid rice combination become available for Boro season and it would be better because rice hybrid perform better under irrigated Boro eco system. One hundrade and nineteen days growth duration also very good for T. Aman season.